The Influence of Lactate and Dipyridamole on Myocardial Fatty Acid Metabolism in Man, Traced with 123l-17-lodo-heptadecanoic Acid - Duwel, C. M. B.; Visser, F. C.; van Eenige, M. J.; Westera, G.; Roos, J. P. (Nuklearmedizin - NuclearMedicine, 1990)
Changes in myocardial metabolism can be detected externally by registration of time-activity curves after administration of radioiodinated fatty acids. In this scintigraphic study the influence of lactate on fatty acid metabolism was investigated in the normal human myocardium, traced with 123l-17-iodoheptadecanoic acid (123l-17-HDA). In patients (paired, n = 7) lactate loading decreased the uptake of 123l-17-HDA significantly from 27 (control: 22-36) to 20 counts/min/pixel (16-31; p <0.05 Wilcoxon). The half-time value increased to more than 60 rriin (n = 5), oxidation decreased from 61 to 42%. Coronary vasodilatation, a well-known side effect of lactate loading, was studied separately in a dipyridamole study (paired, n = 6). Coronary vasodilatation did not influence the parameters of the time-activity curve. These results suggest that changes in plasma lactate level as occurring, among other effects, during exercise will influence the parameters of dynamic 123l-17-HDA scintigraphy of the heart.